Comportamento ecofisiológico de Attalea microcarpa Spruce e Attalea attaleoides Mart., ao longo do gradiente topográfico (platô, vertente e baixio), em uma floresta de terra firme ao norte de Manaus. - Souza, Lissandra Alves de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The availability of primary resources (water, CO2, nutrient availability,light and temperature ) exert selective pressures on plant species thus ecophysiological strategies adopted by each species can determine the success of their establishment in specific environments. The Amazon has high topographic variability that determine the formation of microenvironments with changes in the availability of light, water , nutrients and carbon dioxide concentrations. Assuming that topography imposes conditions that may be limiting for certain species researches are being conducted with the aim of determining the role of topography factors like a predictor of species distribution in Central Amazonia. Whereas plants recognize environmental limits this paper proposed to evaluate the effects of factors that vary according to the topography, which may influence the distribution and abundance of understory palms by affecting the photosynthetic performance of these, conferring adaptive advantages to them, according to the topographical environments where they are. The aim of this study was to investigate the ecophysiological behavior of Attalea microcarpa Spruce and Attalea attaleoides Mart . (palms belong to the botanical family Arecaeae ) along the topographic gradient in an upland forest north of Manaus at two distinct periods of precipitation . The study was conducted at the Adolfo Ducke Forest Reserve , located 26 km northwest of Manaus , the structure and floristic are basically defined by soil type and topography , being : plateau, slope, lowland and campinarana . It was determined the canopy opening through hemispheric camera, variations in specific leaf area (SLA ), the leaf water potential by pressure pump and water use efficiency, the concentrations of nitrogen ( N ) and phosphorus ( P ) and leaf photosynthetic efficiency in the use of nitrogen ( EUN ) and phosphorus (PUE ), the chlorophyll content index with a portable chlorophyll meter, gas exchange and photosynthetic parameters via a infrared gas analyzer ( IRGA ). The average values of Pmax A.microcarpa were 3,65 μmol m - 2 s - 1 and 2,66 μmol m - 2 s - 1 during periods of high and low precipitation , respectively. At A. attaleoides specie during highest precipitation period Pmax were 2,86 μmol m - 2 s - 1 and in periods of low precipitation 2,45 μmol m- 2s - 1 . Light curves of the species studied were similar to those found for other species of understory which are typical values of low-light species. The stomata conductance, transpiration, dark respiration, compensation irradiance, saturation irradiance, quantum efficiency and the water use efficiency showed no significant differences between topographical environments at both species. The differences between periods of precipitation showed that those species exert stomata control avoiding water lost during low precipitation when the evaporative demand is high . The WUE showed higher values during high precipitation at A. attaleoides plants, opposite behavior was observed at A. microcarpa, which could be understood as a result of soil conditions. The light canopy opening indicated shade environments, the average of values were 4,68% at A. attaleoides and 4,65 % at A. microcarpa . The SLA differed among species, being highest at A. attaleoides , than A. microcarpa. The N and P phosphorus did not differ along the topographic gradient. The chlorophyll index showed values around 80 to both species, typical values to understory plants. Although the species have typical understory plants characteristics was not possible to determine ecophysiological behaviors that confer adaptive advantages to those species, according the environment they are found, being require further study over the time. Key-words: topography, palmtrees, species compositions, photosynthesys, nutrients, water potential, leaf, understory.
Keywords: Ecofisiologia; Fotossíntese; Palmeiras